Off-pump mitral valve repair: primary result of treating moderate ischemic mitral regurgitation during off-pump coronary artery bypass grafting - Li, Jingxing; Gu, Chengxiong (Journal of Thoracic Disease, 2019)
Treating moderate ischemic mitral regurgitation (IMR) in patients with coronary artery disease (CAD) undergoing off-pump coronary artery bypass grafting (OPCAB) is arguable and difficult. Mitral valve repair (MVP) is the first choice in treating moderate-to-severe IMR under cardiopulmonary bypass (CPB). In last decade, percutaneous treatment of mitral regurgitation was used in clinic (1,2). Now we proposed and used off-pump mitral valve repair to treat moderate IMR. The left ventricular surface just below coronary sinus was folded. This would reshape the annulus and the left ventricle below the mitral annulus. Sixteen patients with moderate mitral regurgitation underwent off-pump MVP mentioned previously during OPCAB. The surgical procedure is simple. The early results showed that this way is safe and effective.